Assessing electronic cigarette effects and regulatory impact: Challenges with user self-reported device power. (1st October 2017) - Rudy, Alyssa K.; Leventhal, Adam M.; Goldenson, Nicholas I.; Eissenberg, Thomas
Highlights: We examined how well electronic cigarettes (ECIG) users could report liquid and device characteristics. Most users reported liquid nicotine consistent with marketed concentrations. Most participants could not report voltage or resistance. Only 18.2% of participants reported a valid ECIG wattage. Researchers need methods other than self-report to obtain ECIG characteristics. Abstract: Background: Electronic cigarettes (ECIGs) aerosolize liquids for user inhalation that usually contain nicotine. ECIG nicotine emission is determined, in part, by user behavior, liquid nicotine concentration, and electrical power. Whether users are able to report accurately nicotine concentration and device electrical power has not been evaluated. This study's purpose was to examine if ECIG users could provide data relevant to understanding ECIG nicotine emission, particularly liquid nicotine concentration (mg/ml) as well as battery voltage (V) and heater resistance (ohms, Ω) – needed to calculate power (watts, W). Methods: Adult ECIG users (N = 165) were recruited from Los Angeles, CA for research studies examining the effects of ECIG use. We asked all participants who visited the laboratory to report liquid nicotine concentration, V, and Ω. Results: Liquid nicotine concentration was reported by 89.7% (mean = 9.5 mg/ml, SD = 7.3), and responses were consistent with the distribution of liquids available in commonly marketed products. The majority could not report voltage (51.5%) or resistance (63.6%). Of the 40 participants (24.8%) who reported voltage and resistance, there was a substantial power range (2.2–32, 670 W) the upper limit of which exceeds that of the highest ECIG reported by any user to our knowledge (i.e., 2512 W). If 2512 W is taken as the upper limit, only 30 (18.2%) reported valid results (mean 237.3 W, SD = 370.6; range = 2.2–1705.3 W). Conclusions: Laboratory, survey, and other researchers interested in understanding ECIG effects to inform users and policymakers may need to use methods other than user self-report to obtain information regarding device power.